Soil Erosion, Effects and Efficient Solutions: Study in Indian Context: Understanding the impact of soil erosion and implementing sustainable solutions for improved productivity (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Despite the fact that our nation is honored with wide varieties of soils with high fertility, it is being debased step by step by different regular and human activities. Ranchers in India are grumbling about low profitability as a result of different reasons and soil debasement is one of them. Loss of soil fertility results in low efficiency. It additionally results in staggering expense of-creation, low pay, nourishment shortage, loss of biodiversity and so forth. As nourishment security is a noteworthy concern, India needs to defeat the test of low profitability because of soil corruption. Protection of soil is the best way to supersede this issue. This paper put a light with efficient solutions on soil erosion and its effects.